Differentiation-independent fluctuation of pluripotency-related transcription factors and other epigenetic markers in embryonic stem cell colonies - Sustáčková, Gabriela; Legartová, Soňa; Kozubek, Stanislav; Stixová, Lenka; Pacherník, Jiří; Bártová, Eva (Stem cells and development, 2012)
Embryonic stem cells (ESCs) maintain their pluripotency through high expression of pluripotency-related genes. Here, we show that differing levels of Oct4, Nanog, and c-myc proteins among the individual cells of mouse ESC (mESC) colonies and fluctuations in these levels do not disturb mESC pluripotency. Cells with strong expression of Oct4 had low levels of Nanog and c-myc proteins and vice versa. In addition, cells with high levels of Nanog tended to occupy interior regions of mESC colonies. In contrast, peripherally positioned cells within colonies had dense H3K27-trimethylation, especially at the nuclear periphery. We also observed distinct levels of endogenous and exogenous Oct4 in particular cell cycle phases. The highest levels of Oct4 occurred in G2 phase, which correlated with the pKi-67 nuclear pattern. Moreover, the Oct4 protein resided on mitotic chromosomes. We suggest that there must be an endogenous mechanism that prevents the induction of spontaneous differentiation, despite fluctuations in protein levels within an mESC colony. Based on the results presented here, it is likely that cells within a colony support each other in the maintenance of pluripotency.
Keywords: metylace; Animals; antigen Ki-67; Lysine; Green Fluorescent Proteins; lysin; Octamer Transcription Factor-3; FRAP; Pluripotent Stem Cells; Blotting, Western; nanog; G2 fáze; buněčná diferenciace; Cell Nucleus; Proto-Oncogene Proteins c-myc; Mice; oktamerní transkripční faktor 3; homeodoménové proteiny; protoonkogenní proteiny c-myc; kultivované buňky; myši; Methylation; zelené fluorescenční proteiny; buněčné jádro; epigeneze genetická; western blotting; Cells, Cultured; G2 Phase; embryonální kmenové buňky; pluripotentní kmenové buňky; Homeodomain Proteins; nika kmenových buněk; Epigenesis, Genetic; Fluorescence Recovery After Photobleaching; Ki-67 Antigen; Nanog Homeobox Protein; histony; Cell Differentiation; Histones; zvířata; Microscopy, Confocal; konfokální mikroskopie; Stem Cell Niche; Embryonic Stem Cells